2014
DOI: 10.1093/conphys/cou032
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise causes physiological stress and impairs breeding migration behaviour in frogs

Abstract: Noise from human activities is increasing globally. We provide evidence that traffic noise increases glucocorticoid concentrations and impairs reproductive behavior in frogs. Since prolonged stress can compromise health, survival and reproduction, and because impaired reproductive behavior can reduce mating opportunities, these results suggest noise may contribute to amphibian declines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 59 publications
1
70
0
1
Order By: Relevance
“…This could result in systematic genetic differences among 241 populations along light and sound level gradients. We know that the settlement, dispersal, and 242 migration patterns of many organisms are influenced by sound [53] and light [27,34]. We are 243 not, however, aware of investigations into whether these altered patterns of movement, and any 244 subsequent gene flow, have created genetic population differentiation.…”
Section: Sensory Stimuli As Drivers Of Gene Flow 238mentioning
confidence: 99%
“…This could result in systematic genetic differences among 241 populations along light and sound level gradients. We know that the settlement, dispersal, and 242 migration patterns of many organisms are influenced by sound [53] and light [27,34]. We are 243 not, however, aware of investigations into whether these altered patterns of movement, and any 244 subsequent gene flow, have created genetic population differentiation.…”
Section: Sensory Stimuli As Drivers Of Gene Flow 238mentioning
confidence: 99%
“…Among these 23 studies, 70% considered the impacts of noise pollution. For species that use vocalizations to undertaken crucial life history stages (such as song birds and amphibians; [61,62]) or reply on sound to avoid predators, navigate and forage (such as bats and amphibians; [63,64]), any noise that can mask sound can have a detrimental impact. For example, three studies demonstrated that bird diversity decreased as a result of road-related noise [65][66][67].…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
“…A further three studies confirmed that road-related noise influenced the survival and breeding success of wildlife. Among birds, such noise led to smaller clutch sizes [68] and reduced longevity [69], and among amphibians, it induced a stress response and impaired the wood frog's (Lithobates sylvaticus) ability to attract mates [62]. Similarly, a study on Stephen's kangeroo rat (Dipodomys stephensi) found that the sound of passing vehicles induced foot drumming and thus raised concerns that engaging in such false responses could potentially be energetically and biologically costly [70].…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
“…There is growing consensus that risktaking behavior and other aspects of animal "personality" have a genetic component (Stamps and Groothuis, 2010), which could allow selection for road avoidance. There may also be selective pressures for road avoidance besides road-kill: road noise has been shown to increase corticosterone levels in female Wood Frogs (Lithobates sylvaticus) and impair their ability to navigate to male breeding choruses (Tennessen et al, 2014). In addition, clear zones adjacent to roads are sometimes used by predators as efficient movement corridors or hunting areas (James and Stuart Smith, 2000;Colón, 2002;Laurance et al, 2004;Latham et al, 2011).…”
Section: Discussionmentioning
confidence: 99%